Underwater and Surface Swimming Parameters Reflect Performance Level in Elite Swimmers - Pla, Robin; Poszalczyk, Gauthier; Souaissia, Cyrine; Joulia, Fabrice; Guimard, Alexandre (Frontiers in Physiology, 2021)
Although the role of underwater phases is well-known, no study has taken an interest in describing and quantifying the distance and time spent in apnea as a condition for optimal performance. This study aimed to investigate the impact of time and distance spent underwater and surface parameters on the swimming performance of elite swimmers. The performances of 79 swimmers in 100-m freestyle were analyzed (short-course). The underwater and spatiotemporal parameters of three groups have been recorded: finalists of the 2018 World Swimming Championships (WORLD), French swimmers who reached a 100 m performance time under 50 s at the 2018 French National Championships (UND50), and those who reached a 100 m performance time above 50 s (UP50). The WORLD group spent more distance underwater (37.50 ± 4.92 m) in comparison with UND50 (31.90 ± 4.88 m, p < 0.05) and UP50 (31.94 ± 4.93 m, p < 0.01) groups. The total percentage of non-swimming time was higher for WORLD (39.11 ± 4.73%) vs. UND50 (34.21 ± 4.55%, p < 0.05) and UP50 (33.94 ± 5.00%, p < 0.01). In addition, underwater speed was higher for WORLD (2.54 ± 0.05 m/s) compared with UND50 (2.46 ± 0.09 m/s, p < 0.05) and UP50 (2.38 ± 0.11 m/s, p < 0.01). Three parameters among the underwater phases (i.e. distance underwater, speed underwater, and total percentage of non-swimming time) determine the 100-m freestyle short course performance. These data suggest an appropriate focus on specific apnea training to improve underwater skills during short-course swimming performances.